Impact of Radial Arterial Location on Catheter Lifetime in ICU Surgical Intensive Care. (18th April 2023) - Marie, Damien; Dahyot-Fizelier, Claire; Barrau, Stéphanie; Boisson, Matthieu; Frasca, Denis; Jamet, Angeline; Chauvet, Stéphane; Ferrand, Nathan; Pichot, Amélie; Mimoz, Olivier; Kerforne, Thomas
Abstract : OBJECTIVES: The use of arterial catheters is frequent in intensive care for hemodynamic monitoring of patients and for blood sampling, but they are often removed because of dysfunction. The primary objective is to compare the prevalence of radial arterial catheter dysfunction according to location in relation to the radiocarpal joint in intensive care patients. DESIGN: Prospective randomized, controlled, single-center study. SETTING: The surgical ICU of the university hospital of Poitiers in France. PATIENTS: From January 2016 to April 2017, all patients over 18 years old admitted to the surgical ICU and requiring an arterial catheter were included. INTERVENTIONS: Randomization into two groups: catheter placed near the wrist (within 4 cm of the radiocarpal joint) and catheter placed away the wrist. The primary endpoint was the prevalence of dysfunction. We also compared the prevalence of infection and colonization. MEASUREMENTS AND MAIN RESULTS: One hundred seven catheters were analyzed (14 failed placements with no difference between the two groups, and 16 catheters excluded for missing data), with 58 catheters in near the wrist group and 49 in away the wrist group. We did not find any significant difference in the number of catheter dysfunctions between the two groups ( p = 0.56). The prevalence density of catheter dysfunction was 30.5 of 1, 000 catheter days for near the wrist group versus 26.7 of 1, 000 catheter days for away the wrist group. However, we observed a significant difference in terms of catheter-related infection in favor of away the wrist group ( p = 0.04). In addition, distal positioning of the catheter was judged easier by the physicians. CONCLUSIONS: The distal or proximal position of the arterial catheter in the radial position has no influence on the occurrence of dysfunction. However, there may be an association with the prevalence of infections.